Allo-hemodialysis: a novel approach to address the global shortfall in dialysis - Kotanko, Peter (Henry Stewart Talks, 2021)
Limitations in kidney replacement therapy, Conventional hemodialysis, Allo-hemodialysis, Ethical, medical and technical aspects of allo-hemodialysis, Use cases for allo- hemodialysis, Deployment hemodialysis models for allo-hemodialysis, Progress and timeline of allo-hemodialysis deployment